The Design and Implementation of the Test Package for the Serial Output Controller board - Karapetsas, Spyridon (My University, 1981)
The Serial Output Controller is one of the component boards of a Marine Navigation System. Litton Systems (Canada) Limited required the development of a test package for this board to be implemented on the DIGIPACT test station. This report introduc.es the subject of electronic component board testing with an overview of the test equipment and underlying philosophies used by Litton Systems for fault detection and fault diagnosis. The four stages of the test package development process, test plan definition, programming, validation and evaluation are described. The architecture of the DIGIPACT test system is presented as background information.
Keywords: controller board; litton systems; serial output; test package